Reduction of the toxicity of physic nut (Jatropha Curcas Linn.) seeds throufg roasting and fermentation - Bitgue, Kari Ann V. (2003)
The seeds of Physic nut are very rich with fatty and amino acids and the mineral content of the seed cake can be compared to feeds used as fodder. Due to several toxic principles, neither the seeds nor the press cake can be used for animal nutrition. Feeding experiments on 20 10-week-old male mice (M. musculus) for 21 days were carried out to determine reduction of the seed toxicity through roasting and through R. oligosporus Saito fermentation. Mice fed with pigeon pellets showed active behavior, no mortality, no pili erection, normal posture, increasing average weight (0.003 g/day), no gross abnormalities and nectrotic tissues. Mice fed with unfermented seed showed earliest sluggish behavior (day 5), 80% mortality (day 10), pili erection (day 3), humpback posture (day 5), greatest average weight decrease (0.964 g?day), and gross abnormalities, exhibited by liver discoloration and presence of slimy fluid in the abdominal cavity. Mice fed with roasted seed showed sluggish behavior (day 7), 80% mortality (day 15), pili erection (day 4), humpback posture (day 9), average weight decrease (0.735 g/day), and gross abnormality exhibited by enlarged gall bladder. Mice fed with fermented seed showed sluggish behavior (day 14), pili erection (day 7), humpback posture (day 16), average decrease (0.245 g/day); however, only 20% mortality was attained and normal gross anatomy was observed. Results suggest that roasting and fermenting the seeds may have reduced toxicity. Feeding fermented seeds resulted in fewer abnormalities in mice